Accounting 1 - Hussain, HusnamariA; Mazali, Manizah; Nik Ibrahim, Nik Haslina; Abdul Rahman, Noredah; Mohd. Daud, Norhazni; Mohd. Noor, Rohana (IIUM Printing Sdn. Bhd., 2012)
Workbook used by Accounting 1 students of Department of Quantitative Studies of Centre for Foundation Studies, IIUM.